Self-Assembly by Tridentate or Bidentate Ligand: Synthesis and Vapor Adsorption Properties of Cu(II), Zn(II), Hg(II) and Cd(II) Complexes Derived from a Bis(pyridylhydrazone) Compound - Hong-Juan Liu; Rui Yi; Dong-Mei Chen; Chao Huang; Bi-Xue Zhu (Molecules, 2020)
Four complexes, [Cu4L2(OCH3)2(CH3OH)2]·2H2O (1), [Zn2L2Cl4]·2H2O·2CH3OH (2), [Hg2L2Br4]·4CH3OH (3), and {[CdL2Cl2]·4H2O·4CH3OH}n (4), have been synthesized and characterized from a bis(pyridylhydrazone) ligand (L) with copper(II), zinc(II), mercury(II) or cadmium(II), respectively. Complex 1 exists as a centrosymmetric tetranuclear dimer with L as deprotonated tridentate ligand. Complexes 2 and 3 exist as centrosymmetric metallamacrocycles with L as bidentate ligand. Complex 4 exists as a 1D looped-chain coordination polymer. The thermal stabilities and vapor adsorption properties of the four complexes were investigated as well.